Vicarious Learning From Innovative Women Entrepreneurs in Thailand - Dawisa Sritanyarat (2020)
© The Author(s) 2020. The Problem: The number of Thai women entrepreneurs has increased to nearly half of all Thai entrepreneurs over the past years with 80% of them reported to have entered into opportunity-driven entrepreneurship. This growing social phenomenon, however, remains underexplored by limited numbers of academic studies on Thai women entrepreneurship. Extending the understanding of opportunity-driven women entrepreneurs in the changing Thai context is therefore significant for developing national human resources. The Solution: This study highlights the opportunity-driven category of women entrepreneurs defined by Cromie and Hayes as Innovators. Taking the phenomenological approach as a research method, in-depth interviews from 13 innovative women business owners in Thailand were analyzed to understand their motivations, challenges, and success factors, as well as the contemporary worldview of the Thai culture and values concerning gender roles and social norms. The Stakeholders: National policymakers, educators, human resource development professionals, and parents can craft policies and practices that align with key learnings from the lived experiences of women entrepreneurs. Aspiring women entrepreneurs can also vicariously learn from the study participants who serve as role models.